ANALISIS INDEK KEPUASAN MASYARAKAT PDAM KOTA PEKALONGAN - Choliq Sabana; Siti Nurhayati; Alvis Muryodewanto (Fakultas Ekonomi Universitas Pekalongan, 2016)
Public services such as those operated by PDAM Pekalongan City still found manyweaknesses that can not meet the expected quality of the community . It is characterized by thepresence of various public complaints . the importance of serving the water supply PDAM Pekalonganconsiders it important for information to the Public Satisfaction Index (HPI ) in order to improve qualityof service Surveys are intended to : 1 ) Identify and analyze the weaknesses of each of the elements ofservice delivery PDAM Pekalongan and 2 ) Measure the community Satisfaction Index (HPI ) PDAMKota Pekalongan . The survey results show that, in general , PDAM service performance Pekalongancategorized as